C-Reactive Protein Enhances IgG-Mediated Cellular Destruction Through IgG-Fc Receptors in vitro - Temming, A. Robin; Tammes Buirs, Matthias; Bentlage, Arthur E. H.; Treffers, Louise W.; Feringa, Hannah; de Taeye, Steven W.; Kuijpers, Taco W.; Nagelkerke, Sietse Q.; Brasser, Giso; Mok, Juk Yee; van Esch, Wim J. E.; van den Berg, Timo K.; et al. (Frontiers in Immunology, 2021)
Antibody-mediated blood disorders ensue after auto- or alloimmunization against blood cell antigens, resulting in cytopenia. Although the mechanisms of cell destruction are the same as in immunotherapies targeting tumor cells, many factors are still unknown. Antibody titers, for example, often do not strictly correlate with clinical outcome. Previously, we found C-reactive protein (CRP) levels to be elevated in thrombocytopenic patients, correlating with thrombocyte counts and bleeding severity. Functionally, CRP amplified antibody-mediated phagocytosis of thrombocytes by phagocytes. To investigate whether CRP is a general enhancer of IgG-mediated target cell destruction, we extensively studied the effect of CRP on in vitro IgG-Fc receptor (FcγR)-mediated cell destruction: through respiratory burst, phagocytosis and cellular cytotoxicity by a variety of effector cells. We now demonstrate that CRP also enhances IgG-mediated effector functions towards opsonized erythrocytes, in particular by activated neutrophils. We performed a first-of-a-kind profiling of CRP binding to all human FcγRs and IgA-Fc receptor I (FcαRI) using a surface plasmon resonance array. CRP bound these receptors with relative affinities of FcγRIa= FcγRIIa/b= FcγRIIIa> FcγRIIIb= FcαRI. Furthermore, FcγR blocking (in particular FcγRIa) abrogated CRP’s ability to amplify IgG-mediated neutrophil effector functions towards opsonized erythrocytes. Finally, we observed that CRP also amplified killing of breast-cancer tumor cell line SKBR3 by neutrophils through anti-Her2 (trastuzumab). Altogether, we provide for the first time evidence for the involvement of specific CRP-FcγR interactions in the exacerbation of in vitro IgG-mediated cellular destruction; a trait that should be further evaluated as potential therapeutic target e.g. for tumor eradication.